Bengal Partitions – a Study: The Impact of Partition on Bengal (Journal of Advances and Scholarly Researches in Allied Education, 2016)
There were two Bengal partitions; one occurred in1905 and another in1947. In 1905, Bengal was divided into three provinces, and the official reasonprovided by the British Raj was that the Bengal Presidency was too big to ruleproperly. In 1911, fortunately for the Bengalis, the British Raj was forced towithdraw the first Bengal partition, whereas in 1947, India was divided intotwo countries, India and Pakistan, and Bengal was divided into western andeastern regions. The western part of the Bengal province became the state ofWest Bengal and remained with India, whereas the eastern part of Bengal becameEast Pakistan. The main reason for the partition of India in 1947 was to put astop to the constant struggles and violent outbursts between Hindus andMuslims. It was assumed by the British Raj, the Indian Congress leaders and theMuslim League leaders that by dividing India into two separate nations andgiving each dominant religious sect control over its respective country, theHindus could live peacefully in India and the Muslims could live peacefully inPakistan. Unfortunately because of the partition, hundreds of thousands ofdeaths occurred and the millions of people became refugees. Partition failed tosolve the religious problems and left a grave impact on the Indians andPakistanis. The brutality and carnage of which some were the perpetrators, somewere driven by greed to grab the properties and orchards of other neighbors,and how some used religious hatred to seize it during the time of partition, onboth sides. How the women, we claim to respect so much were treated, theunprecedented scale on which women were raped, killed and mutilated by bothHindu Indians, Muslim Indians. From this suffering arose a mutual hatred, aseach religious group blamed the other for its losses. From that hatred emergeda relentless rivalry and a mutual urge to avenge past sufferings. The tensioncreated in 1947 seemed to have a long-lasting impact on the Bengalis, andstories about the suffering of ancestors who relocated from East Pakistan orWest Pakistan are still told among families. Shortly after Pakistan wascreated, west and east parts of Pakistan started to grow apart based on theircultural and language differences. In 1971, with the help of Indian military,East Pakistan finally declared its independence from Pakistan and became aseparate nation-state called Bangladesh.